Crop residue preparation and utilization - Aberra, Adie; Getahun, Elizabeth; Bezabih, Melkamu; Worku, Tigist (International Livestock Research Institute, 2024)
Crop residues, the straws of cereals (barley, wheat, teff etc.) and pulses (faba bean, field peas, chickpeas etc.), are used as animal feed in Ethiopia. The feed preparation process followed by farmers in North Shewa Zone is explained in this document.